HUBUNGAN ANTARA KEMAMPUAN MEMBACA PEMAHAMAN DENGAN MENYELESAIKAN SOAL CERITA MATEMATIKA SISWA KELAS IV - ., I Made Arya Praditha; ., Dra. Nyoman Kusmariyatni,S.Pd; ., Drs.I Gusti Ngurah Japa,M.Pd (MIMBAR PGSD Undiksha, 2017)
Penelitian ini bertujuan untuk (1) mendeskripsikan kemampuan membaca pemahaman siswa, (2) mendeskripsikan kemampuan menyelsesaikan soal cerita Matematika siswa (3) mengetahui hubungan antara kemampuan membaca pemahaman dengan menyelesaikan soal cerita Matematika siswa kelas IV semester II tahun pelajaran 2016/2017 di gugus I Kecamatan Banjar Kabupaten Buleleng. Jenis penelitian ini adalah penelitian expost-facto. Populasi penelitian ini adalah seluruh siswa kelas IV semester II tahun pelajaran 2016/2017 di gugus I Kecamatan Banjar Kabupaten Buleleng yang berjumlah 135 orang siswa. Sampel penelitian ini adalah seluruh siswa kelas IV semester II tahun pelajaran 2016/2017 di gugus I Kecamatan Banjar Kabupaten Buleleng yang berjumlah 135 orang siswa. Data kemampuan membaca pemahaman dengan tes membaca sedangkan untuk kemampuan menyelesaikan soal cerita Matematika menggunakan intrumen soal esay. Data yang dikumpulkan dianalisis menggunakan analisis statistik Deskriptif dan Korelasi Person Product Moment. Berdasarkan hasil analisis data, menunjukan bahwa thit > ttab, sehingga dapat diinterpretasikan bahwa terdapat hubungan yang berarti atau signifikan antara kemampuan membaca pemahaman dengan menyelesiakan soal cerita. Dari rata-rata hitung, bahwa rata-rata kemampuan membaca pemahaman > rata-rata menyelesaikan soal cerita Matematika, sehingga dapat disimpulkan bahwa ada hubungan yang berarti atau signifikan antara kemampuan membaca pemahaman dengan kemampuan menyelesaikan soal cerita Matematika siswa kelas IV di Gugus I Kecamatan Banjar Kabupaten Buleleng.Kata Kunci : kemampuan membaca pemahaman, menyelesaikan soal cerita, cerita Matematika This study aims to (1) describe reading comprehensipnm students, (2) to describe the ability to solve the problem of Mathematics story of the students (3) to know the relationship of ability reading comprehensipnm students with the solve the story of Mathematics of the fourth grade students of semester II of academic year 2016/2017 in cluster I Banjar District, Buleleng Regency. This type of research is an expost-facto study. The population of this study is all students of class IV semester II of academic year 2016/2017 in cluster I Banjar District Buleleng Regency, which amounted to 135 students. The sample of this research is all students of class IV semester II of academic year 2016/2017 in cluster I Banjar Sub-district Buleleng Regency which amounted to 135 students. Data from the reading comprehensipnm students is collected by reading test while for the ability to solve the problem of Mathematics using the instrument about essay. The data collected were analyzed using Descriptive statistics analysis and Person Product Moment Correlation. Based on the results of data analysis, so that it can be interpreted that there is a significant or significant relationship between the reading comprehensipnm students with the ability to completing story problem. From the average count. This means that average the ability reading comprehensipnm students > average to solve the problem of Mathematics story, so it can be concluded that there is a significant or significant relationship between the ability reading comprehensipnm students with the to solve the problem story of Math grade IV students in Cluster I Banjar District Buleleng Regency.It This means that average ability reading comprehensipnm students > average to solve the problem of Mathematics story, so it can be concluded that there is a significant relationship between the ability reading comprehensipnm students with the ability to solve the problem of Mathematics story of fourth grade students in Gugus I Banjar Sub-district, Buleleng Districtkeyword : ability reading comprehensipnm students, solve mathematics story problem, matematics story